2007
DOI: 10.1016/j.biopsycho.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate improves deficient error evaluation in children with ADHD: An event-related brain potential study

Abstract: Children with ADHD make more errors than control children in response-conflict tasks. To explore whether this is mediated by enhanced sensitivity to conflict or reduced error-processing, task-related brain activity (N2, Ne/ERN, Pe) was compared between 8- to 12-year-old children with ADHD and healthy controls during performance of a flanker task. Furthermore, effects of methylphenidate were investigated in ADHD children in a second study. ADHD children made more errors, especially in high-response-conflict con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
97
6
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 67 publications
14
97
6
1
Order By: Relevance
“…In children with DSM-III-R defined ADHD who completed a Flanker task, both ERN and Pe were reported to be larger on error than correct response trials as expected, with reduced Pe indicating reduced error awareness in the clinical group (Jonkman et al, 2007;see Table 2). In a mixed-subtype AD/HD group with a large proportion of participants with comorbid ODD, reduced ERN after errors in a Flanker task was interpreted as a performance monitoring deficit (van Meel et al, 2007).…”
Section: Performance Monitoringsupporting
confidence: 61%
See 1 more Smart Citation
“…In children with DSM-III-R defined ADHD who completed a Flanker task, both ERN and Pe were reported to be larger on error than correct response trials as expected, with reduced Pe indicating reduced error awareness in the clinical group (Jonkman et al, 2007;see Table 2). In a mixed-subtype AD/HD group with a large proportion of participants with comorbid ODD, reduced ERN after errors in a Flanker task was interpreted as a performance monitoring deficit (van Meel et al, 2007).…”
Section: Performance Monitoringsupporting
confidence: 61%
“…Participants respond with a button-press to the direction of a target arrow and ignore distracter stimuli flanking the target, which may be congruent, incongruent, or neutral with regard to the target. Jonkman et al (2007) reported that children with DSM-III-R defined ADHD and controls showed larger N2 to correct compared to incorrect incongruent trials, with a trend towards larger N2 overall for ADHD indicating enhanced sensitivity to conflict caused by the flanker stimuli.…”
Section: Flanker Taskmentioning
confidence: 99%
“…In the flanker task, children with AD/HD show slower RTs and lower response accuracy than typically-developing children for all stimulus types (Johnstone et al, 2010;Jonkman et al, 2007;Konrad et al, 2006). Compared to typically-developing children, children with AD/HD also show a more delayed RT to incongruent stimuli compared to neutral stimuli (Jonkman et al, 2007;Ridderinkhof et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…Compared to typically-developing children, children with AD/HD also show a more delayed RT to incongruent stimuli compared to neutral stimuli (Jonkman et al, 2007;Ridderinkhof et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Given that ERN and Pe are typically ascribed to ACC (Falkenstein, Hohnsbein, Hoormann, & Blanke, 1991;Gehring, Goss, Coles, Meyer, & Donchin, 1993;Herrmann, Rommler, Ehlis, Heidrich, & Fallgatter, 2004;Posner & Dehaene, 1994), this suggests an impairment of ACC in ADHD patients. In addition, dopamine agonists restore the Pe amplitude (Groen, et al, 2008;Jonkman, van Melis, Kemner, & Markus, 2007). Moreover, neuroimaging studies document metabolic hypoactivation (Bush, et al, 1999;Rubia, et al, 1999) and hypotrophy of ACC (Makris, et al, 2007;Makris, et al, 2010;Seidman, et al, 2006).…”
Section: Acc Dysfunction In Adhdmentioning
confidence: 98%